Síntesis de nanopartículas de óxidos de hierro y cobalto como alternativa potencial antimicrobiana frente a microorganismos con alta resistencia usando como modelo Acinetobacter baumannii y Aspergillus brasiliensis (2024)
This study addresses the synthesis and characterization of cobalt nanoparticles (CoNPs) and their potential in antimicrobial applications. Its effectiveness was investigated against the multidrug-resistant bacteria Acinetobacter baumannii and the fungus Aspergillus brasiliensis, a food contaminant of clinical importance. The nanoparticles were synthesized by ultrasound-assisted chemical reduction, and their characterization included techniques such as scanning transmission electron microscopy (STEM), infrared spectroscopy (FTIR) and vibrating sample magnetometry (VSM).